Pusat Sastra Di Pekanbaru Dengan Pendekatan Arsitektur Ekspresionis - Sri Handayani; Wahyu Hidayat; R Lisa Suryani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Literature work is a tool used by authors that contains ideas about works of art. Language in literature works becomes a tool to createa special feeling that contains aesthetic value, apart from being a means of communication, which is able to convey various kinds ofinformation to the audience or reader. Today's literature art has begun to be abandoned by the society because it is less attractive tothe younger generation. This appalling condition has resulted in the absence of quality works from Riau writers today. In addition tothe disappearance of the printed newspapers that previously provided space for literature, the space for friendship between literarycommunities seems to have been cut off. Related to this, Pekanbaru needs a Center for Literature Arts that can function as a mediumand medium for appreciation of the development of literary arts. To achieve this goal, the Center for Literary Arts is designed withvarious facilities that can support literary arts development activities such as educational, production and recreation facilities. DesignMethods of the Center for Literature Arts in Pekanbaru with an Expressionist Architectural Approach. The infinity concept waschosen as a concept in the design of the Center for Literary Arts to be unlimited from writers in their work. This concept is a responseto the functions and themes of design and building, namely Expressionist Architecture, which explains that creativity has noboundaries. Apart from having an educational purpose, this design also displays visuals that can express imagination. The researchmethod used are including field data collection, literature study and empirical studies. The design results with the Infinity concept thatadopts the form and meaning of the application principles of Expressionist Architecture. The interesting shape of the building, theatmosphere of the shape is created by the use of building colors that inspire enthusiasm, and the use of varied material elements thatplay a role in conveying the message of the meaning of the building.Keywords: Center for Literature Arts, Architecture Expressionist, Infinity.